Bargaining with the Machine : Technology, Surveillence, and the Social Contract - Pallitto, Robert M., 1964- (Book collections on Project MUSE., 2020)
"Cell phone apps share location data in exchange for giving users a more detailed and unique experience. Software companies store user data in cloud storage in exchange for allowing users to access their files from any computer. Biometric scanners read fingerprints in exchange for improved security. Employees at a Swedish company agreed to have microchips implanted in their hands in exchange for greater convenience in opening doors and buying food. As technology becomes ever more inescapable, the ability to freely consent to these exchanges becomes increasingly unclear. Robert Pallitto uses the social theory of bargaining to explore the daily compromises we make with technology. We effectively bargain with the machine by giving up certain freedoms (e.g., privacy) in exchange for benefits (e.g., convenience), but is resistance to such bargains still possible when the technologies are backed by pervasive, and often coercive, corporate and state power? What do the liberal concepts of freedom and choice mean when our choices are already to a great extent determined by the technologies structuring our existence? Can we still talk about a social contract, when we are not always aware of the agreements we are making, the benefits we receive come with hidden costs, and the state is allied with corporate and military interests that receive benefits at the expense of the people? Bargaining with the Machine examines these thorny and complex questions by exploring the various "irresistible bargains" that confront people today"--